Loss of Identity in the Acting Sphere - Čale Feldman, Lada (2009)
The paper addresses two instances in which the actor is proclaimed to be an entity without identity, Diderot's paradox and Ridout's stage-fright. Confronting Lacoue-Labarthe's reading of Diderot's famous treatise with Miroslav Krleža's treatment of stage-fright in his short story "Behind the Mask", the paper argues that the representation of the two phenomena of acting experience entails a loss of discursive identity.
Projekt MZOS
ENG